Continuous vs. Discontinuous (Teleport) Locomotion in VR: How Implications can Provide both Benefits and Disadvantages - Riecke, Bernhard E.; Zielasko, Daniel (2021 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2021)
In this short paper we provide a comparative overview of the implications of using continuous vs. discontinuous (teleport) locomotion methods in VR, and argue how many of these implications can provide both benefits and disadvantages depending on the overall goal, desired user experiences, application scenario/context, as well as individual preferences and one's propensity for cybersickness.
Keywords: Conferences; Cybersickness; NSERC DG 2026; Three-dimensional displays; User interfaces; Virtual Reality, locomotion in VR, continuous locomotion, discontinuous locomotion, teleporting, cybersickness, motion sickness, sensory conflicts, locomotion control, effort, presence, immersion; conferencePapers; proj--teleport-vs-continuous